2016
DOI: 10.1016/j.gene.2016.06.031
|View full text |Cite
|
Sign up to set email alerts
|

POLD1: Central mediator of DNA replication and repair, and implication in cancer and other pathologies

Abstract: The evolutionarily conserved human polymerase delta (POLD1) gene encodes the large p125 subunit which provides the essential catalytic activities of polymerase δ (Polδ), mediated by 5’–3’ DNA polymerase and 3’–5’ exonuclease moieties. POLD1 associates with three smaller subunits (POLD2, POLD3, POLD4), which together with Replication Factor C and Proliferating Nuclear Cell Antigen constitute the polymerase holoenzyme. Polδ function is essential for replication, with a primary role as the replicase for the laggi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 195 publications
(243 reference statements)
1
116
0
Order By: Relevance
“…Hearing impairments constitute the most common features in MDPL syndrome, although they are not always found [14,15,17]. The POLD1 gene is expressed in all cells; therefore, the associated deafness may be a consequence of axonal neurons not functioning efficiently [27]. Among the female patients, only three patients had primary/secondary amenorrhea including our case [10,13,17], whereas the others reported a regular menstrual cycle.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Hearing impairments constitute the most common features in MDPL syndrome, although they are not always found [14,15,17]. The POLD1 gene is expressed in all cells; therefore, the associated deafness may be a consequence of axonal neurons not functioning efficiently [27]. Among the female patients, only three patients had primary/secondary amenorrhea including our case [10,13,17], whereas the others reported a regular menstrual cycle.…”
Section: Discussionmentioning
confidence: 72%
“…Notably, our comparative analysis (Table 3) suggested that premature atherosclerosis with hypertension, cardiovascular diseases, and neoplasm might be less prevalent in MDPL compared with Werner syndrome [24] and other laminopathies [32]. Several germline mutations in POLD1 exonuclease domains are also known to predispose carriers to cancers, particularly colorectal and endometrial cancers [14,27]. However, to date at the age of 46 years, the patient has not presented any malignant disease.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…DNA hypomethylation was also observed at some key genes involved in male fertility, viz. GAMT (Schmidt et al, ) and TACC3 (Aitola, Sadek, Gustafsson, & Pelto‐Huikko, ) and at the DNA repair genes POLD1 (Nicolas, Golemis, & Arora, ) and EVL (Schultz et al, ) .…”
Section: Discussionmentioning
confidence: 99%